Makna Keterbukaan dan Implementasi Pancasila sebagai Ideologi Terbuka - Vivi Elizabeth (Faculty of Law Hang Tuah University, 2022)
Pancasila is the ideological basis of Indonesia. Increasingly, it can be seen that there are fewer Indonesian people who apply the characteristics of the Pancasila ideology. Ideology has an important function in compiling and instilling confidence in the concept of the ideals of the state to its citizens so that it can be a source of inspiration in realizing ideals. In this journal article the author uses normative research methods as a type of legal research that focuses on pure law and positive law. The author uses the type of qualitative research analysis. Where this type of analysis has a system of collecting data and theories of books, journals, and websites that are in line with the research chosen by the author. In the sense of an open ideology, there is a flaw in the idea that does the openness of an ideology mean that all forms of ideology and interpretation can be swallowed up? It should be remembered that the open nature here is to interact with the surrounding environment which is focused on the instrumental value, not just the basic value.